Margin Analysis of Fresh Sea Fish Caught from Fishermen in Berkah Sea Warehouse, Rantau Panjang Village, Pantai Labu District, Deli Serdang Regency - Gusniati, Putri; M. Nawawi, Zuhrinal; Dharma, Budi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Sea fish is one of the commodities that have high popularity in Indonesia. Efforts to improve the quality of the fisheries sector will have a major impact on consumers as well as the expansion of the marketing system being implemented. The purpose of this study was to determine the marketing margins of fresh sea fish caught by fishermen at the Berkah Sea Warehouse, Rantau Panjang Village, Pantai Labu District, Deli Serdang. This research uses a descriptive method with a mixed-method approach. The data sources used are primary data and secondary data, by observing and interviewing. The results of this study indicate that the fish marketing channel in the Berkah Sea Warehouse begins with fishermen as producers, fish warehouse toke, wholesalers, retailers, and final consumers. The pattern of marketing channels in this marine fish sales system has three categories. The marketing margin analysis shows that the highest total margin is in marketing channel I for tuna Rp. 20,000 and for mackerel fish Rp. 21,000. In the second marketing channel, the total margin for tuna is Rp. 17,000 and Mackerel fish Rp. 20,000. Total marketing margin with less value on marketing channel III by showing the amount of Rp. 10,000 for tuna and mackerel fish Rp. 13,000. The value of the fisherman’s share or the share received by the producer from the three types of marketing patterns is more profitable in the third marketing channel with a percentage value of fisherman's share above 50% and classified as efficient marketing.